Pengaruh Rekrutmen Dan Kompensasi Terhadap Kinerja Guru Pada SMK Swasta HKBP (STM) Pematangsiantar - Darwin Lie; Marisi Butarbutar; Erbin Chandra; Efendi Efendi; Amurisi Zega (Program Studi Magister Ilmu Manajemen Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2021)
Objective. The aims of this study were: To determine the recruitment, compensation and performance of teachers at the HKBP Private Vocational School (STM) Pematangsiantar. This study aims to determine the effect of recruitment and compensation on teacher performance at the HKBP Private Vocational School (STM) Pematangsiantar. Research Methods. The research design used in writing this research is library research and field research. The data collection techniques used in this research are the questionnaire method, the interview method and the documentation method. Results. The results of this study can be concluded that: Recruitment, compensation, and teacher performance is good. Recruitment and compensation have a positive influence on teacher performance. Recruitment and compensation have a strong and positive relationship to teacher performance. The good or bad performance of teachers can be explained by recruitment and compensation. Conclusion. Based on the results of the correlation coefficient test and the coefficient of determination, the results obtained which state that there is a strong and positive relationship between recruitment and compensation on teacher performance at the HKBP Private Vocational School (STM) Pematangsiantar simultaneously. Based on the simultaneous test (F test), the results obtained which state that recruitment and compensation have a positive and significant effect on the performance of teachers at the HKBP Private Vocational School (STM) Pematangsiantar simultaneously. Based on the partial test (t test), the results state that recruitment and compensation have a positive and significant effect on teacher performance